Functions of several variables - Fleming, Wendell (Undergraduate texts in mathematics, 1977)
Euclidean spaces - Elementary topology of "E" - Differentiation of real-valued functions - Vector-valued functions of several variables - Integration - Curves and line integrals - Exterior algebra and differential calculus - Integration on manifolds - Appendices.